The Effectiveness of the ODOW Strategy in Developing Young Learners’ English Vocabulary - Ekka Zahra Puspita Dewi; Siti Ngaisah; salma Hira; darmanto darmanto (Jurnal Ilmu Multidisiplin, 2025)
This study investigated the effectiveness of the One Day One Word (ODOW) strategy to enhance English as a Foreign Language (EFL) vocabulary mastery among elementary school students. This classroom action research (CAR) involved sixty-three fourth-grade students as research subjects. The preliminary test revealed that 57 out of 63 subjects struggled with basic vocabulary translation from Indonesian to English, scoring below 75 out of 100 on items taken directly from their textbook. The research proceeded with a cyclical approach consisting of four key stages: planning, action, observation, and reflection The initial results from Cycle 1 demonstrated some improvement, with 41 out of 63 students achieving an average score of 70 out of 100. Then, this research implemented cycle 2. The results of cycle 2 were significantly more promising, with 60 out of 63 students achieving an average score of 91 out of 100. The findings showed that the ODOW strategy was beneficial for improving young learners’ vocabulary mastery in an EFL context. In addition, the findings indicated that consistent, focused exposure to new vocabulary, coupled with active engagement and practice, could lead to significant gains in vocabulary acquisition.